War in the woods : Estonia's struggle for survival, 1944 - 1956 - Laar, Mart, 1960- 1960- (Compass Press, 1992)
With the Soviet reoccupation after World War II, Estonians faced a choice of submitting to Communist puppets or trying to survive in the traditional refuge of their forests while waiting for help from the West which never came. Those who chose the second course, Estonia's "Forest Brothers," mounted an armed resistance which, for more than a decade, seriously challenged Soviet rule. This is their story, told for the first time by sources within Estonia. This account is drawn from interviews with Forest Brothers who survived and relatives of those who died, and from documents and photographs from Soviet KGB files. It reflects Estonian courage and humor, the faith and sacrifice of a people suppressed, and the indomitable determination of a free nation to regain independence.